Leveraging the strengths of mice, human stem cells, and organoids to model pancreas development and diabetes - Lorberbaum, David S.; Sarbaugh, Dylan; Sussel, Lori (Frontiers in Endocrinology, 2022)
Diabetes is an epidemic with increasing incidence across the world. Most individuals who are afflicted by this disease have type 2 diabetes, but there are many who suffer from type 1, an autoimmune disorder. Both types of diabetes have complex genetic underpinnings that are further complicated by epigenetic and environmental factors. A less prevalent and often under diagnosed subset of diabetes cases are characterized by single genetic mutations and include Maturity Onset Diabetes of the Young (MODY) and Neonatal Diabetes Mellitus (NDM). While the mode of action and courses of treatment for all forms of diabetes are distinct, the diseases all eventually result in the dysfunction and/or death of the pancreatic  cell - the body’s source of insulin. With loss of  cell function, blood glucose homeostasis is disrupted, and life-threatening complications arise. In this review, we focus on how model systems provide substantial insights into understanding  cell biology to inform our understanding of all forms of diabetes. The strengths and weaknesses of animal, hPSC derived -like cell, and organoid models are considered along with discussion of GATA6, a critical transcription factor frequently implicated in pancreatic dysfunction with developmental origins; experimental studies of GATA6 have highlighted the advantages and disadvantages of how each of these model systems can be used to inform our understanding of  cell specification and function in health and disease.